Dedifferentiated Low-Grade Central Osteosarcoma of the Mandible - Kenji Yamagata; Naomi Ishibashi-Kanno; Ryota Matsuoka; Fumihiko Uchida; Satoshi Fukuzawa; Hiroki Bukawa (Hindawi Limited, 2022)
We present the first, to our knowledge, case of a dedifferentiated low-grade central osteosarcoma (LCOS) of the mandible. A 48-year-old Japanese woman underwent enucleation under general anesthesia after a diagnosis of ossifying fibroma. At the second recurrence, the pathological diagnosis after biopsy was of sarcoma with MDM2(+) and CDK4(+) immunohistochemical staining results. Hemimandibulotomy, supraomohyoid neck dissection, and free-flap reconstruction with a rectus abdominal flap were performed. A retrospective reevaluation of the first specimen with additional immunohistochemical staining for MDM2 and CDK4 yielded a final diagnosis of dedifferentiated LCOS. The patient showed no recurrence or lung metastasis 3 years after the final surgery.